Blue-light-dependent inhibition of twitching motility in Acinetobacter baylyi ADP1: additive involvement of three BLUF-domain-containing proteins - Bitrian, Mariana (2013)
Twitching motility in Acinetobacter baylyi ADP1 is inhibited by moderate intensities of blue light in a temperature-dependent manner (maximally at 20 °C). We analysed the involvement of four predicted blue-light sensing using flavin (BLUF)-domain-containing proteins encoded in the genome of this strain in the twitching motility phenotype. All four genes were expressed both in light and in darkness. A phylogenetic tree showed that one BLUF domain, ACIAD2110, grouped separately from the other three (ACIAD1499, ACIAD2125 and ACIAD2129). Individual knockout mutants of the latter three, but not of ACIAD2110, fully abolished the light dependency of the twitching motility response. Quantitative analysis of transcript level of the three genes showed a decreased expression in the light, with dark/light ratios of 1.65±0.28, 1.79±0.21 and 2.69±0.39, for ACIAD2125, ACIAD2129 and ACIAD1499, respectively. Double and triple knockouts of ACIAD1499, ACIAD2125 and ACIAD2129 confirmed the same phenotype as the corresponding single knockouts. Complementation of all the single knockouts and the triple knockout mutants with any of the three BLUF-domain-encoding genes fully restored the inhibition of twitching motility by blue light that is observed in the wild-type strain. A. baylyi ADP1 therefore shows a high degree of redundancy in the genes that encode BLUF-containing photoreceptors. Moreover, all plasmid-complemented strains, expressing any of the BLUF proteins irrespective of the specific set of deleted photoreceptors, displayed increased light-dependent inhibition of twitching motility, as compared to the wild-type (P<0.001). We conclude that the three genes ACIAD1499, ACIAD2125 and ACIAD2129 are jointly required to inhibit twitching motility under moderate blue-light illumination.